NURSING CARE FOR HEART FAILURE PATIENTS: INEFFECTIVE BREATHING PATTERN WITH SEMI-FOWLER POSITION INTERVENTION - Joko Febriyanto; Erlina Windyastuti; Ari Pebru Nurlaily (Journal of Advanced Nursing and Health Sciences, 2026)
Background: Heart failure is a clinical syndrome characterized by the inability of the heart to pump blood adequately to meet the body’s oxygen and nutrient requirements. Non-pharmacological nursing interventions, including positioning, can support respiratory function and improve oxygenation. This study aimed to describe nursing care for a heart failure patient with an ineffective breathing pattern by applying the semi-Fowler position.Methods: This study employed a descriptive case study design using a nursing care approach. The subject was one adult patient diagnosed with NYHA I–II heart failure who presented with dyspnea, hypoxia, and an ineffective breathing pattern. The case was conducted at Panti Waluyo Hospital in Surakarta on February 5, 2025. The intervention consisted of positioning the patient in a 45° semi-Fowler position for 15 minutes, combined with oxygen administration at 10 LPM via a non-rebreather mask. Oxygen saturation was assessed before and after the intervention.Results: After 15 minutes of the 45° semi-Fowler position combined with oxygen administration, oxygen saturation increased to 99%, representing a 9% increase. The patient also reported a reduction in shortness of breath, although the ineffective breathing pattern had not completely resolved.Conclusion: The use of a 45° semi-Fowler position for 15 minutes, combined with oxygen therapy, may be considered a non-pharmacological nursing intervention to support oxygenation and respiratory comfort in patients with heart failure.